Do cloisonné ao liriforme: diacronias de um adorno de vestuário na alta Idade Média - Arezes, Andreia (2017)
This article focuses on a particular set of metallic artefacts used over costume: the belt-buckles recovered from the Portuguese territory, dated from the 5th century till the beginning of the 8th. My analysis and interpretation developed in order to sort the elements that were included in the inventory according to a typology. It was possible to distinguish three major groups of objects that reflect different scenarios and influences namely through the technical and aesthetic solutions adopted. It is important to mention that the corpus of materials inventoried was not retrieved exclusively from burial sites. Actually, their origin is very diverse. It was possible to indicate, as source location, Roman or Late Roman villae, sometimes connected tonecropolis or, for instance, habitats or shelters. In other cases, however, their origin is completely unknown, which raises more difficulties for interpretation. In the microcosm of a grave, the set of artefacts that accompanied the individual could integrate belt-buckles. But it should be noted that a grave might not necessarily be a reflection of everyday life, in that it may reveal a specific composition to the act of burial. On the other hand, it is advanced the hypothesis of each of the artefacts deposited was related to the condition, gender or ethnicity of the buried individual. In this sense, it is very likely that certain kinds of objects could have been used to transmit and perpetuate the sense of belonging to a particular group. This point, amongst several others, will be explored in this article. Despite its inherent limitations, it aims to discuss the informations provided by the dress adornments and to articulate them with the contemporary events and with the underlying mentality.